Constitucionalismo brasileiro e multiculturalismo a afirmação das diferenças religiosas - Nakano, Vinícius Wagner de Sousa Maia (2017)
It is investigated the way in which constitutionalism, multiculturalism and religion are related dialogically in the construction of identities and religious differences throughout the history of Brazilian constitutionalism. Religious identities erect boundaries that establish conceptual and semiotic limits and barriers, influencing behaviors and ways of thinking, as well as the ways in which subjects represent and self-represent their religious condition. This influences how the state produces laws and how state agents interpret and enforce laws. Identities and differences translate into the discursive plane in the figures of different subjects, statements and discourses, which often collide with each other. In addition, boundaries and barriers have changed in the course of history, which can be noted in the discursive plane, in the way in which the concept of religion was constructed juridically, despite the historical enunciation of religious freedom and worship in the texts Of Brazilian constitutions. This concept was altered when new actors began to question the hegemonic discourse of a Catholic matrix, incorporated into the discourse of the State for the long period of validity of the royal patron, and after, when attempting to construct the national identity. Adepts of different religions, as different discursive actors, throughout this historical path, have lived in a complex network of power relations, in which belonging to a particular religion can mean - in terms of a look of a subject that integrates a hegemonic discourse - be associated, with illicit practices, with distrust, contempt, prejudice and discrimination. The re-signification of this association has only occurred in the face of the emergence of new discursive, counter-hegemonic actors and the empowerment of minorities and vulnerable groups, previously silenced, invisible and denied in their own condition of being and existence. The changes can be attributed, in part, to the processes of secularization and pluralism that have made constitutionalism possible as a normative theory of politics, which imposes limits on the power of the state and guarantees human and fundamental rights, and especially praxis Dialogical in the Bakhtinian sense, which makes possible the coexistence of different subjects, statements and religious discourses in the same political community. In this way different religious practices have migrated from the field of illegality to the field of lawfulness, although this does not imply that the perception of religious freedom is experienced in the same way by the different actors from their own discourses.